2021
DOI: 10.1080/20008198.2020.1869399
|View full text |Cite
|
Sign up to set email alerts
|

Functional disconnection and reconnection: an alternative strategy to stoicism in public safety personnel

Abstract: Background: North American public safety personnel (PSP; e.g., police, firefighters, paramedics) training programmes often focus on the importance of controlling emotional reactions (i.e. remaining stoic) to make sound decisions in high-stress environments. Many PSP carry avoidant coping strategies into their personal lives, however, resulting in disrupted relationships and deterioration of well-being. Objective: We argue for an alternative perspective, functional disconnection and functional reconnection (FD/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Fourth, BOS introduces functional disconnection and functional reconnection (FD/FR;McElheran and Stelnicki, 2021). There is an argument that effective physicians enter an "action mode, " setting aside emotional reactions and focusing on following protocol to prevent a patient's death (Whitehead, 2014, p. 273).…”
Section: The Before Operational Stress (Bos) Programmentioning
confidence: 99%
“…Fourth, BOS introduces functional disconnection and functional reconnection (FD/FR;McElheran and Stelnicki, 2021). There is an argument that effective physicians enter an "action mode, " setting aside emotional reactions and focusing on following protocol to prevent a patient's death (Whitehead, 2014, p. 273).…”
Section: The Before Operational Stress (Bos) Programmentioning
confidence: 99%
“…Features of Stoic philosophy which appear to have significantly appealed to those engaged in military and PSP occupations include: the Dichotomy of Control (i.e., recommending a focus on that which is within an individual's sphere of influence versus those things that are external); Amor Fati, which directly translated means to "love your fate"; and, the Simplicity of Lifestyle, whereby the Stoics espoused a minimalist approach to life and the avoidance of luxuries (Sellars, 2006;Sherman, 2007). For those working in occupations which often require tolerance of hardship, the suggestion by the Stoic philosophers that virtue and a valued life could be achieved through adherence to these principles likely influenced its adoption in military and PSP cultures (McElheran & Stelnicki, 2021).…”
Section: Stoicismmentioning
confidence: 99%
“…Within my work as a clinician and trainer in contemporary PSP organizations, I (MM) have observed that the ancient Stoic traditions often manifest in the organizational encouragement of PSP members developing and maintaining mastery over thoughts, feelings, and attitudes, particularly within chaotic or stressful circumstances (McElheran & Stelnicki, 2021). Some PSP training programs tend to emphasize repetitive engagement in contrived critical incident circumstances to enhance recruits' ability to maintain calm in the face of highly stressful circumstances (Atkins & Norris, 2011).…”
Section: Stoicismmentioning
confidence: 99%
See 1 more Smart Citation
“…Shell Shock and hysteria were recognized as legitimate diagnoses resulting from exposure to war but soldiers with such conditions were considered inherently psychologically weak persons who would have still experienced mental health challenges had they remained civilians ( Duguid, 1938 ; Horswill and Carleton, 2021 ). Remnants of such thinking persist today regarding PSP ( Burns and Buchanan, 2020 ; Ricciardelli et al, 2020a ), as evidenced by cultures of stoicism in policing organizations ( McElheran and Stelnicki, 2021 ) and the use of personality screening measures with police recruits not only to assess for vocational goodness of fit, but also for the potentiality for psychological problems ( Pozzulo et al, 2017 ). Nevertheless, the ability of personality screens to predict mental health outcomes among police appears modest at best ( Detrick et al, 2001 ; Koepfler et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%